Neonatal necrotizing enterocolitis complicated by glutaric acidemia type II: a case report - Zhang, Yuli; Chen, Longfei; Duan, Miao (Frontiers in Pediatrics, 2025)
Glutaric acidemia type II (GAII) is an autosomal recessive genetic metabolic disorder associated with mitochondrial dysfunction, characterized by multiple acyl-CoA dehydrogenase deficiency that affects fatty acid metabolism. Necrotizing enterocolitis (NEC) represents a severe inflammatory condition affecting premature neonates. This report describes a case involving a male preterm infant born at a gestation of 30 + 1 weeks who developed NEC complicated by GAII. On the eighth day of life, the patient exhibited abdominal distension and vomiting. Diagnostic imaging, including abdominal B-ultrasound and x-ray, revealed thickened bowel walls, multiple intestinal pneumatosis, and partial intestinal dilation, consistent with NEC. Subsequent recurrent episodes of acidosis, hyperlactacidemia, and hypoglycemia were observed. Diagnosis of GAII was confirmed through tandem mass spectrometry analysis of a blood sample. Genetic metabolic diseases may complicate or mimic common infections, leading to potential misdiagnosis. A differential diagnosis of GAII should be considered when active anti-infective treatments fail.